Hubungan Pengetahuan dan Motivasi Bidan dengan Pelaksanaan 1000 Hari Pertama Kehidupan di Wilayah Kerja Puskesmas Jatinangor dan Puskesmas Cisempur - Nafillah, Nafillah; Astuti, Sri; Didah, Didah; Rinawan, Fedri Ruluwedrata; Sari, Puspa (Jurnal Kesehatan Vokasional, 2020)
Background : Indonesia one of the developing countries that still has nutritional problems in pregnant women, nursing mothers and infants aged zero to two years. The First Thousand Days of Life (1000 HPK) is a movement to improve nutrition with the aim of pregnant women, nursing mothers and infants aged zero to two years. Midwives are health workers involving 1000 HPK. The impact of not doing 1000 HPK by midwives in pregnant women and toddlers, one of which occurs anemia in the assessment, lack of chronic energy (KEK) in pregnant women and giving birth to stunting babies.Objective : To determine the relationship between knowledge and motivation of midwives with the implementation of 1000 HPK in the Jatinangor Health Center and Cisempur Health Center Work Areas.Methods : Quantitative with cross-sectional design. The sampling technique used total sampling with a large sample of 41 midwives. Data analysis using chi-square test. This research was conducted in the work area of Jatinangor Health Center and Cisempur Health Center in August 2018.Results : This study showed no significant relationship between knowledge and implementation of 1000 HPK (p> 0.05) and there was a significant relationship between motivation and implementation of 1000 HPK (p <0.05).Conclusion : There is no relationship between the knowledge of midwives and the implementation of 1000 HPK and there is a relationship between the motivation of midwives and the implementation of 1000 HPKKeywords : First 1000 Days of Life, Motivation of Midwives, Implementation of 1000 HPK, Knowledge.